DPA calculation in a stainless steel baffle of Chooz-A PWR using auto-dosimetry measurements - Bourganel Stéphane; Galia Antonio; Hure Jérémy; Bonzom Rémy; Domain Christophe; Gosmain Cécile-Aline (EPJ Web of Conferences)
This paper presents a method dedicated to the calculation of DPA (displacements per atom) in a stainless steel element irradiated inside Chooz-A reactor core. This method is based on experimental results obtained in samples taken from the analyzed stainless steel element, and calculation results. Experimental results consist in the mass of 59Co and the activity of 60Co, both measured in 2018, i.e. 27 years after the final shutdown of Chooz-A reactor. Calculations are carried out with the TRIPOLI-4® 3D Monte Carlo particle transport code, and the DARWIN/PEPIN2 depletion code, with a simplified modelling of Chooz-A reactor. As explained in this paper, these simplifications are corrected by the use of measurement results. Due to a lack of information about the irradiated steel element (initial 59Co quantity in particular), an iterative process was developed and used. It allows to evaluate missing information and to calculate corrected DPA results in samples. Besides, stress tests were carried out to check the robustness of the process and the uniqueness of DPA result for each sample. This work was carried out by CEA/SERMA with the financial support of EDF.